Multiband integrated antennas for 4G terminals - Sánchez-Hernández, David A. (Artech House antennas and propagation library., 2008)
Get the very latest details on the cutting-edge antennas that will be integrated in complex 4th generation wireless communications systems with this first-of-its-kind volume. Written by a panel of leading experts in the field, the book serves as a comprehensive, one-stop resource, including in-depth coverage of multiband integrated antenna design, simulation, testing and manufacturing. This practical book helps you solve integration problems for ever-increasing multiband requirements. You find discussions on important considerations regarding future handset MIMO terminals, such as efficiency and the effect of the user. The book also shows you how to avoid tweaking for fractal multiband designs and printed dipole design. Moreover, you learn how to identify and choose suitable multiband techniques for a particular MIMO handset. Supported with over 100 illustrations, this forward-looking resource presents the most recent design developments in the field, so you don't need to spend valuable time searching through scattered journal articles for the details you need